Analysis of proper position of extraction roadway on roof in high-strength gas emission workface: A case study of Zhaozhuang coal mine in southern Qinshui Basin. (November 2021) - Wang, Wei; Zhang, Jianwei; Chen, Xiangjun; Liu, Yanwei; Li, Hong; Wang, Haifeng; Fang, Zhiming
Abstract: When mining high-rank coals with strong adsorption and weak desorption, the fully mechanized mining face of a thick coal seam under full-seam mining may encounter broken coal, surrounding rock and instantaneous release of large amounts of gas into the mining space from adjacent coal seams due to mining stress relief, which is extremely likely to cause gas overrun accidents at the working face. At present, the major gas control method adopted to solve this problem is the directional drainage of the fractured zone in the mining area through a roof extraction roadway (RER). However, the drainage effect is closely related to its horizontal distance from the return airway and its vertical distance from the coal seam roof. Based on the analysis of fracture characteristics in different areas of the overlying strata above the gob, this paper elaborates the extraction mechanism of RER, and employs three methods: RER at different positions, directional long borehole on roof (RDLB) at different horizontal and vertical positions, and numerical simulation of the stress release effect of the overlying rock, to investigate the gas drainage effect in mining area. A method to determine the best drainage location in the gob based on the stress release ratio of the overlying rock is proposed. The results show that either RERs or RDLBs work to conduct directional drainage in the mining area; the best position is 25 m from the return airway of the mining face horizontally and 50–55 m from the coal seam roof vertically. The research methods provide insight for later studies concerning highly gassy mines and coal and gas outburst mines. Moreover, the research results serve as guidance for other mines with similar mining conditions.